Pengaruh Locus of Control, Ethical Sensitivity, Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Spiritual dan Tingkat Pendidikan Terhadap Perilaku Etis - Astuti, Rika; Sugiharto, Bambang; kurniawan, Asep (Universitas Pendidikan Indonesia, 2019)
Abstract. The purpose of this study was to determine the effect of locus of control, ethical sensitivity, intellectual intelligence, emotional intelligence, spiritual intelligence and education level on ethical behavior in accounting students of vocational high schools (SMK) and accounting students in Subang. This research is included in research with quantitative data. The sample in this study were 407 respondents consisting of SMK accounting students and accounting students in Subang. The sample selection technique used is probability sampling while for sampling in this study using simple random sampling. The method used for data collection is the survey method through a questionnaire or questionnaire. The data analysis technique used is descriptive statistical analysis and infective statistical analysis. The results showed that locus of control, ethical sensitivity, intellectual intelligence, spiritual intelligence, and education level had a positive and significant effect on the ethical behavior of SMK accounting students and accounting students in Subang. While emotional intelligence does not affect the ethical behavior of SMK accounting students and accounting students in Subang